2017
DOI: 10.15360/1813-9779-2017-1-17-23
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Severe Birth Asphyxia on the Hemostasis System in Newborns During the First Hour of Life

Abstract: У новорожденных с тяжелой интранатальной асфиксией отмечается нарушение адаптации системы ге мостаза, в связи с этим они имеют высокий риск кровотечений в течение первых суток жизни.Цель исследования -оценить влияние перенесенной тяжелой асфиксии в родах и метаболического ацидоза на состояние системы гемостаза у новорожденных.Материалы и методы. Провели ретроспективный анализ историй болезни 40 новорожденных, рож денных в тяжелой асфиксии (1 я группа), и 20 «здоровых» новорожденных (2 я группа). Исследование п… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 2 publications
(8 reference statements)
0
2
0
Order By: Relevance
“…This study also described lower values of coagulation factors V and VIII in some asphyxiated neonates, as well as increased FDPs, implying a higher frequency of DIC in this group. Golub et al, 41 using TEG in asphyxiated and healthy term neonates from blood extracted within the first hour of life, reported that asphyxiated newborns had prolonged R and K and reduced α-angle and MA, findings compatible with a hypocoagulable profile in this group. Hathaway et al 42 performed coagulation testing on cord blood in neonates of high-risk pregnancies and reported that though infants with fetal distress had increased levels of factors V and VIII, they were not hypercoagulable; R + K parameter and antithrombin were within normal limits.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…This study also described lower values of coagulation factors V and VIII in some asphyxiated neonates, as well as increased FDPs, implying a higher frequency of DIC in this group. Golub et al, 41 using TEG in asphyxiated and healthy term neonates from blood extracted within the first hour of life, reported that asphyxiated newborns had prolonged R and K and reduced α-angle and MA, findings compatible with a hypocoagulable profile in this group. Hathaway et al 42 performed coagulation testing on cord blood in neonates of high-risk pregnancies and reported that though infants with fetal distress had increased levels of factors V and VIII, they were not hypercoagulable; R + K parameter and antithrombin were within normal limits.…”
Section: Resultsmentioning
confidence: 87%
“…Thieme. All rights reserved 41. using TEG in asphyxiated and healthy term neonates from blood extracted within the first hour of life, reported that asphyxiated newborns had prolonged R and K and reduced α-angle and MA, findings compatible with a hypocoagulable profile in this group.…”
mentioning
confidence: 85%